2015
DOI: 10.1007/jhep09(2015)126
|View full text |Cite
|
Sign up to set email alerts
|

A new phase for the anisotropic N=4 super Yang-Mills plasma

Abstract: Black hole solutions of type IIB supergravity have been previously constructed that describe the N=4 supersymmetric Yang-Mills plasma with an anisotropic spatial deformation. The zero temperature limit of these black holes approach a Lifshitz-like scaling solution in the infrared. We show that these black holes become unstable at low temperature and we construct a new class of black hole solutions which are thermodynamically preferred. The phase transition is third order and incorporates a spontaneous breaking… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 50 publications
(116 reference statements)
0
57
0
Order By: Relevance
“…Let us also comment on the novelty of our approach. There are several previous holographic works which provide anisotropy, see, e.g., [8][9][10][11][12][13][14][15][16][17][18][19]. The main difference between our model and other anisotropic models in the literature is that in our case the anisotropy is produced by the presence of dynamical objects (the D5-branes of the multiple layers) and not by fluxes or fields depending anisotropically on the coordinates.…”
Section: Introductionmentioning
confidence: 87%
“…Let us also comment on the novelty of our approach. There are several previous holographic works which provide anisotropy, see, e.g., [8][9][10][11][12][13][14][15][16][17][18][19]. The main difference between our model and other anisotropic models in the literature is that in our case the anisotropy is produced by the presence of dynamical objects (the D5-branes of the multiple layers) and not by fluxes or fields depending anisotropically on the coordinates.…”
Section: Introductionmentioning
confidence: 87%
“…We can distinguish two cases depending on whether n > 1 or n < 1, with a limiting case n = 1 between the two. The master function has the following 1 In the case m = 4 we could still have T D5 00 > 0 if the density of D5 branes is small enough Q f ≤ 4(n+3) 9 (the subleading term is positive when the bound is saturated), however, we will not study this possibility. IR expansions, depending on the value of n,…”
Section: Ir Regimementioning
confidence: 99%
“…This in principle could lead to the observation of stars more compact than the ones allowed by isotropic matter, see, e.g., [3,4]. Strongly coupled anisotropic phases have been studied using holography in a variety of setups, including axionic/dilatonic sources [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], electric [21][22][23] and magnetic fields [24][25][26][27][28][29][30][31][32][33] or both [34][35][36][37][38], and p-wave superfluids [39][40][41][42][43][44]. Strongly coupled holographic matter has also been studied in the context of compact stars [45][46][47][48][49][...…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, already some time before MT, the authors of [57] found a solution of Einstein's equation corresponding to an anisotropic energy momentum tensor (with two pressures) and they analyzed the quasinormal modes for R-charge diffusion. The recent paper [58] obtained a new solution which, apart from the dilaton and axion, has an extra scalar field X. They argued that this new solution is thermodynamically preferred over the MT one at low temperatures.…”
Section: Introductionmentioning
confidence: 99%